1998
DOI: 10.1002/(sici)1097-4636(199808)41:2<278::aid-jbm13>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Modification of glassy carbon surfaces with synthetic laminin-derived peptides for nerve cell attachment and neurite growth

Abstract: Interactions between cultured nerve cells and surfaces are of importance for the implantation of biocompatible electrode materials such as glassy carbon (GC). Since implants serve as recording sensors in prosthetic neuroscience, we investigated whether coating electrodes with certain laminin derivatives containing the peptide sequences SIKVAV, CDPGYIGSR, PDSGR, YFQRYLI, and RNIAEIIKDA influences neuronal adhesion and neurite outgrowth in vitro. The coating of GC was performed by electrochemical polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 49 publications
0
36
1
1
Order By: Relevance
“…The results are in agreement with other reports in the literature. 20,21 Applications for the IKVAV peptide-grafted coating technology include developing tracts for guidance of neurite growth on implant surfaces and coating areas around recording/stimulation sites to promote neurite growth near the sites for optimal signal transfer between neurons and implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are in agreement with other reports in the literature. 20,21 Applications for the IKVAV peptide-grafted coating technology include developing tracts for guidance of neurite growth on implant surfaces and coating areas around recording/stimulation sites to promote neurite growth near the sites for optimal signal transfer between neurons and implants.…”
Section: Discussionmentioning
confidence: 99%
“…For surface coatings with neurite growth-promoting activity, the laminin-based peptide SRARKQAASIKVAVSADR (Bachem) was utilized. Studies by Thanos et al 20,21 showed that this peptide is very effective in promoting neurite growth in vitro.…”
Section: Covalent Coupling Of Bioactive Peptides To Dextrancoated Basmentioning
confidence: 99%
“…Since then many studies in neuronal patterning have been performed in a variety of labs, using various methods, including surface modification by silane chemistry 113 137 Ti, 140 polystyrene, 130,131 Teflon (fluorinated ethylene propylene), [132][133][134][141][142][143][144] and biodegradable polymers. 145 These studies mainly yielded insights into the adhesion and guidance of neuronal growth by insoluble factors and could prove valuable for selective neuronal immobilization on future microsensors.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 99%
“…These structures are constructed primarily to mimic known peptide sequences such as the RGD and YIGSR cell attachment motifs. 11,[62][63][64][65] In this study, we present a novel collagenmimetic sequence, composed of nine or ten repeats of the sequence (GPNl), that has cell binding activity through an "RGD-independent" mechanism. Although we have not studied extensively the mechanism of cell attachment to this collagen-mimetic molecule, we believe that the ␣2␤1 integrin complex is involved.…”
Section: Discussionmentioning
confidence: 99%